CHANDLER AND ANNUAL WOBBLES BASED ON SPACE-GEODETIC MEASUREMENTS - Hopfner J. (My University, 2003)
In this study, we examine the major components of polar motion, focusing on quantifying their temporal variability. In particular, by using the combined Earth orientation series SPACE99 computed by the Jet Propulsion Laboratory (JPL) from 1976 to 2000 at daily intervals, the Chandler and annual wobbles are separated by recursive band-pass filtering of the x1- and x2- components. Then, for the trigonometric, exponential, and elliptic forms of representation, the parameters including their uncertainties are computed at epochs using quarterly sampling. The characteristics and temporal evolution of the wobbles are presented, as well as a summary of estimates of different parameters for four epochs.
Keywords: POLAR MOTION; CHANDLER WOBBLE; ANNUAL WOBBLE; REPRESENTATION (TRIGONOMETRIC, EXPONENTIAL, ELLIPTIC); PARAMETER; VARIABILITY; UNCERTAINTY